HISTOMORPHOLGICAL STUDY OF CILIARY BODY AND CILIARY PROCESS IN ONE HUMPED CAMEL (CAMELUS DROMEDARIUS) - Shakir Mahmood. Mirhish; Razak J. M; S.H; AL-Maliki (Basrah Journal of Veterinary Research)
Ten eyes (5 right + 5 left ) of five healthy one humped camels (3 male +2 females) aged between (8-12) years old, brought from Shulla slaughter house at Baghdad governorate -Iraq. The study showed that the ciliary body located at the base of iris inside the eye ball (Topographically at limbus) in histological section of eye ball appeared as triangular area.The microscopical examination observed the ora ciliaris retinae ( line of ending Retinae and choroid ) this site represent limits and indicate the area of gradually changed choroid to ciliary body, which posses (111-115) ciliary prosses act as site of zonulary ligament attachment. That important in modification of eye lens during vision